(untitled) (Research, Society and Development, 2021)
Introduction: The prevalence of chronic non-communicable diseases (CNCDs) has increased in recent decades, and neoplasms appear in second place deserving prominence in the current scenario. The experience of changing social roles accompanied by feelings of anxiety, abandonment and loneliness is called social pain, which most often accompanies the cancer patient. This article aims to know and understand the causes of social pain in cancer patients eligible for home palliative care. Methodology: This is an integrative literature review with bibliographic search of the last five years, in the PUBMED database, using the following research guiding question: What are the causes of social pain of people with cancer eligible for palliative care in home care? Results: After analyzing the criteria, 3 articles were defined for review because they met the selection criteria. Conclusion: The causes of social pain involve activities of daily living, changing roles, isolation and loneliness. Palliative care and home care play a valuable role in addressing, preventing and providing relief from social pain, however, there is a lack of knowledge on the part of health professionals on this topic, which can be better addressed in educational institutions.